EFFORTS IN 1ST GRADE OF MADRASAH IBTIDAIYAH NURUL IKHSAN PILANGSARI TO INCREASE THE ABILITY TO RECOGNIZE LETTERS THROUGH KARSUN (ARRANGEMENT-BASED CARTOON) (International Journal of Education and Literature, 2022)
This research is based on the many types of student writing errors and the inability to distinguish letters in 1st grade at Madrasah Ibtidaiyah Nurul Ikhsan in Baleraja Village, Pilangsari Kasun. The purpose of this research was to improve children's ability to recognize letters of the alphabet by employing the use of media. This study is a Classroom Action Research (CAR) involving 13 students from Madrasah Ibtaaiyah Nurul Ikhsan, Class I. This study's instrument is an observation guide, and its technique is a descriptive quantitative approach. Using the KARSUN (arrangement-based cartoon) medium appears to improve the capacity to recognize alphabetic letters, as demonstrated by the study's findings. The results of the observation activity (pre-cycle) yielded a percentage of 7.7%, the results of the first cycle (pretest) yielded a percentage of 23.1%, and the results of the second cycle (posttest) yielded a larger percentage that met the criteria for developing as expected and exceedingly well, namely 53.8%. The ability of grade I (one) students of Madrasah Ibtaiyah Nurul Ikhsan to recognize the letters of the alphabet can thus be enhanced by employing KARSUN (arrangement-based cartoon) media.